Biocompatibility of Acetazolamide and Its Association with Calcium Hydroxide in Rat Subcutaneous Tissue - Lazarotto, Carolina; Johann, Aline Cristina Batista Rodrigues; Carneiro, Everdan; Bettega, PatrÃcia Vida Cassi; Westphalen, VÃ¢nia Portela Ditzel (Iranian Endodontic Journal, 2018)
Introduction: The aim of this study was to evaluate the biocompatibility of acetazolamide and its association with the calcium hydroxide in rat subcutaneous tissues as an intracanal medication for an avulsed tooth. Methods and Materials: Three medications with acetazolamide base were evaluated: group 1 liquid acetazolamide associated with calcium hydroxide powder (LACH); group 2 liquid acetazolamide (LA); and group 3 acetazolamide powder associated with physiological saline (PAPS). The calcium hydroxide associated to physiological saline represented the control group. The medications were implanted in subcutaneous tissues of thirty-nine male rats for 7, 15 and 45 days; after surgery the animals were sacrificed and the sections were stained with hematoxylin and eosin to be evaluated qualitatively or semi-quantitatively with an optical microscope. The inflammation intensity and type of inflammatory cells and the repair process, were assessed. The obtained data were statistically compared through the Kruskal-Wallis test conducted at the 5% level of significance. Results: On the seventh day, there was statistically significant difference between PAPS and LA, in relation to the number of neutrophils (P=0.0016). There was a statistically significant difference in the total number of inflammatory cells in PAPS compared to LACH (P=0.0038) on the fifth day. The total number of inflammatory cells from PAPS was significantly higher in relation to LACH (P=0.0038), as well as LA from LACH (P=0.0038) on forty fifth day. A statistically significant reduction in the value of lymphocytes was also observed in LACH (P=0.0072) and LA (P=0.0010) groups in the same period. Conclusion: The results of this animal study suggest that the association of the liquid acetazolamide with the calcium hydroxide promoted an inflammation reduction and a faster repair process than in the LA and PAPS groups evaluated in 15 and 45 days. Keywords: Acetazolamide; Calcium Hydroxide; Root Resorption